WERS the validity? A critique of the 2004 workplace employment relations survey of employees - Andrew R. Timming (The University of Manchester, Manchester Business School, 2008)
The Workplace Employment Relations Survey series is a tremendously useful source of data for industrial relations researchers. But, like all large-scale secondary datasets, it has a number of design problems. These have not been articulated previously in much depth. Looking at the 2004 instalment of the series, this paper aims to offer a critical appraisal of the survey of employees. The structure of the questionnaire and the validity of the items are critiqued. Recommendations are offered for the next edition of the Workplace Employment Relations Survey.
Keywords: 330; questionnaire design; validity; workplace employment relations survey; Beschäftigung; Arbeitsbeziehungen; Arbeitsmarktforschung; Kritik; Großbritannien